(untitled) (Mustansiria Dental Journal, 2018)
Aims of the study: This study is designed to evaluate some of the dental and skeletal dimensions of individuals with normal and excessive lower anterior facial height and to establish the effect of these two groups (normal and excessive lower anterior facial height) on dento-facial structures for Iraqi adult sample at 18-25 years of age with skeletal and dental CL I occlusion. Material and Method: The sample consisted of (80) previously taken lateral cephalometric radiographs (40 males and 40 females).The sample was divided into two groups (normal lower anterior facial height group and excessive lower anterior facial height group) each of them composed of 40 subjects (20 males and 20 females) Results: The results showed that all linear measurements were significantly larger in males than females in two groups. No significant differences in most of dentoskeletal dimensions were found between the two groups. Highly significant differences for lower anterior dental height (LADH) and upper posterior dental height (UPDH) were found between the two groups. Conclusion: Four anatomical parts were responsible for the variation of the lower anterior facial height upper anterior dental height (UADH) , lower anterior dental height (LADH) , upper posterior dental height (UPDH) and the inclination of the mandibular plane in relation to the anterior cranial base (SN-MP angle).